2022
DOI: 10.1007/s00403-022-02404-5
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic study on nail plate assessment: differences in nail plate shape, thickness, power Doppler signal and scanning approach

Abstract: Ultrasonography (US) of the nail is raising interest in the last years and its feasibility, quickness and amount of descriptive data may provide valuable information. Different authors presented several scanning approaches to nail complex in different pathological conditions, such as psoriasis, but no scanning protocol was ever proposed using healthy subjects as population of reference. The aim of the study was to establish a protocol for the US of nail plate and to assess whether the measurement of the nail p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
0
9
1
2
Order By: Relevance
“…Of the five parameters assessed in this study, only nail plate thickness and distance from the center of the distal phalange to the nail plate have been addressed by other authors using ultrasound, although the available data refer to the hand (Bellinato et al, 2022; Cecchini et al, 2009; De Rossi et al, 2021; Idolazzi et al, 2018; Idolazzi et al, 2019; Marina et al, 2016; Mondal et al, 2018; Naredo et al, 2019; Ureyen et al, 2018; Wortsman et al, 2004), and therefore any interpretation is problematic because there is evidence to support differences between the two models (hand and foot). For nail plate thickness, the literature includes a study on the toenail unit (Mingorance Álvarez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the five parameters assessed in this study, only nail plate thickness and distance from the center of the distal phalange to the nail plate have been addressed by other authors using ultrasound, although the available data refer to the hand (Bellinato et al, 2022; Cecchini et al, 2009; De Rossi et al, 2021; Idolazzi et al, 2018; Idolazzi et al, 2019; Marina et al, 2016; Mondal et al, 2018; Naredo et al, 2019; Ureyen et al, 2018; Wortsman et al, 2004), and therefore any interpretation is problematic because there is evidence to support differences between the two models (hand and foot). For nail plate thickness, the literature includes a study on the toenail unit (Mingorance Álvarez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The literature includes studies on ultrasound parameters of the nail, in all cases in the fingernail unit (Bellinato et al, 2022; Cecchini et al, 2009; De Rossi et al, 2021; Idolazzi et al, 2018; Idolazzi et al, 2019; Mondal et al, 2018; Naredo et al, 2019; Wollina et al, 2001; Wortsman et al, 2004). Only two of these studies (Bellinato et al, 2022; Cecchini et al, 2009) were performed on healthy participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the thicknesses of the nail plates decreased from the first to the fifth finger, in accordance with the literature. 23 In studies conducted with PsA patients, nail plate thicknesses were found to be between 0.15 and 0.86 mm. 24,25 The high level of variability between measurements may be related to patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in PsA cases, the nail bed thicknesses were measured between 1.76 and 2.5 mm. [20][21][22][23][24][25][26] Some studies reported that the nail bed thickness above 2.0 mm should be defined as a sign of nail PsO. 6,27 In contrast to other studies, Marina et al found no significant difference in the nail bed thicknesses of PsA cases compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%